PERCEPATAN INOVASI TEKNOLOGI PEMANFAATAN JERAMI PADI FERMENTASI SEBAGAI PAKAN SAPI POTONG PADA MUSIM KEMARAU - Batseba M.W. Tiro; Petrus A. Beding (Agros Journal of Agriculture Science, 2023)
One of the effective dissemination methods for disseminating the technology produced is using direct communication techniques, namely through field meetings and technology degrees. A field meeting and technology degree on the use of fermented rice straw as cattle feed was held in Telaga Sari village, Kurik district, Merauke Regency, which aims to accelerate the delivery of rice straw fermentation technology and its use as beef cattle feed. Based on this study it can be concluded: 1). There was an increase in the nutritional value of fermented rice straw compared to no fermentation, 2). There was an increase in calf birth weight and weaning weight in the introduction pattern using fermented rice straw compared to the farmer pattern, namely 25.5 ± 1.06 kg and 63.4 ± 1.78 kg. Likewise, the average daily gain (ADG) of calves up to 3 months of age in the introduction pattern was higher than the farmer pattern, namely 0.42 ± 0.02 kg/head/day vs 0.35 ± 0.02 kg/head/day; sow weight change up to 3 months after calving in the introduction pattern was higher than the farmer pattern, namely 0.04 ± 0.05 kg/head/day vs -0.08 ± 0.05 kg/head/day, 3). The technology studied and deployed is technically easy to implement and develop; socially culturally acceptable and applicable, as well as attracting the interest of farmers because it can provide an alternative supply and reserve of feed during the dry season, 4). Dissemination of information on the technology of making fermented rice straw to around 55 stakeholders, namely the Regional Government, agricultural extension, farmers and Agricultural Vocational Schools as well as being covered by TVRI Papua. INTISARISalah satu metode diseminasi yang efektif untuk mendesiminasikan teknologi yang dihasilkan adalah menggunakan teknik komunikasi langsung yaitu melalui temu lapang dan gelar teknologi. Temu lapang dan gelar teknologi pemanfaatan jerami padi fermentasi sebagai pakan sapi dilaksanakan di kampung Telaga Sari, distrik Kurik, Kabupaten Merauke, yang bertujuan untuk mempercepat penyampaian teknologi fermentasi jerami padi dan pemanfaatannya sebagai pakan sapi potong. Berdasarkan kajian ini dapat disimpulkan : 1). Terjadi peningkatan nilai nutrisi jerami padi fermentasi dibandingkan tanpa fermentasi, 2). Hasil kajian menunjukkan bahwa terjadi peningkatan berat lahir pedet dan berat sapi pada pola introduksi dengan memanfaatkan jerami padi fermentasi dibandingkan pola petani yakni 25,5 ± 1,06 kg dan 63,4 ± 1,78 kg. Rataan PBB pedet sampai umur 3 bulan pada pola introduksi lebih tinggi dibanding pola petani yakni 0,42 ± 0,02 kg/ekor/hari vs 0,35 ± 0,02 kg/ekor/hari; perubahan berat badan induk sampai 3 bulan setelah beranak pada pola introduksi lebih tinggi dibanding pola petani yakni 0,04 ± 0,05 kg/ekor/hari vs -0,08 ± 0,05 kg/ekor/hari. 3). Teknologi yang dikaji dan digelar, secara teknis mudah diterapkan dan dikembangkan; secara sosial budaya dapat diterima dan diterapkan, serta menarik minat petani karena dapat memberikan suatu alternatif penyediaan dan cadangan pakan pada musim kemarau, 4). Didesiminasikannya informasi teknologi pembuatan jerami padi fermentasi kepada sekitar 55 stakeholder orang yakni Pemerintah Daerah, penyuluh, petani dan SMK Pertanian serta diliput oleh TVRI Papua